China-US rivalry as a factor in the development of modern Russian-American relations - León Ortega, Helen Sugelly (2020)
The history of Russian-American relations, especially in the past two centuries, shows the permanent tension between the two countries along with the limitations of cooperation and mutual understanding. In this framework, this article investigates whether the complicated relations between the United States and China in the Trump era are a factor that influences modern Russian-American relations. For this purpose, a documentary investigation was carried out, concluding that China affects the context of Russian-American relations, although it is not an obstacle or an engine for bilateral dialogue, it does exert significant influence by pressing Moscow to assume a more active position in the formation of a new world order.